KAJIAN PENATAAN LANSKAP JALAN VETERAN DI KOTA MALANG - Tanggela, Ardian; Nuraini, Nuraini; Djoko, Riyanto (Universitas Tribhuwana Tunggadewi, 2018)
Development of the town always followed with the construction of city facilities are adequate. One of them, namely adequate road infrastructure. The potential in the build Setup me-dian road solution specifically conceived on the main street of Malang on Veteran Street Malang se-like the green line has an important role in improving the quality of the environment, and the quality must be observed in order not to experience a decrease. The purpose of this research is to examine the Setup or knowing the landscape in the median Veteran Street Malang. The penelian method is used in the data retrieval method using ob-servasi and inventory, data collection consists of primary data and secondary data. The type and amount of vegetation that is in the median of the road Veteran Malang i.e. totalling 40 type of vegetation including Elephant Grass (Pennisetum Purpureum), Baby Blue (Nemophila menziesii), Decorative Broccoli (Enodia), Peanut (Arachis pintoi) Ornamental, Paris (Lili Chlorophytum comosum), Bronjol/Ornamental Onion (Zephyranthes candida), White Jaburan (Ophiopogon jaburan) tea-tehan (Acalypha siamensis), Ornamental Banana (Calathea lutea), Codiaeum Variegatum (Codiaeum variegatum) Gecko, galangal (Alpinia purpurata), Song of India ( Dracaena reflexa), Palm Sadeng (Saribus rotundifolius), Codiaeum Variegatum (Codiaeum variegatum) Bali, mahogany (Swietenia mahagoni), Trembesi (Samanea saman), Soka (modern Ixora coccinea), (Cerbera manghas) Bintaro etc. Based on the observations in what research it can be concluded that the characteristics Setup/layout vegitatiton median that is on the main street of Malang is pretty good just need a cleaner Setup so that it can further beautify and increased the green line's aesthetic value in the way Veteran Malang Kajian Penataan Lanskap Jalan Veteran di Kota Malang. Fakultas Pertanian Program Studi S1 Arsitek Lanskap Universitas Tribhuwana Tunggadewi Malang. Pembimbing I : Riyanto Djoko, SP., MP, Pembimbing II : Nuraini, S.Sarl., M.Si. Pembangunan kota selalu diikuti dengan pembangunan fasilitas kota yang memadai. Sa-lah satunya yaitu prasarana jalan yang memadai. Potensi dalam membangun penataan me¬dian jalan kususnya di jalan utama Kota Malang tepatnya di Jalan Veteran Kota Malang se¬bagai jalur hijau mempunyai peranan penting dalam meningkatkan kualitas lingkungan, dan kualitas tersebut harus diperhatikan agar tidak mengalami penurunan. Tujuan dari penelitian ini yaitu untuk mengkaji atau mengetahui penataan lanskap di median jalan Veteran Kota Malang. Metode penelian yang digunakan dalam pengambilan data menggunakan metode ob¬servasi dan inventarisasi, pengumpulan data terdiri dari data primer dan data sekunder. Jenis dan jumlah vegetasi yang ada di median jalan Veteran Kota Malang yaitu berjumlah 40 jenis veg-etasi diantaranya Rumput Gajah (Pennisetum Purpureum), Baby Blue (Nemophila menziesii), Brokoli Hias (Enodia), Kacang Hias (Arachis pintoi), Lili Paris (Chlorophytum comosum), Bawang Bronjol/ Hias (Zephyranthes candida), Jaburan Putih (Ophiopogon jaburan)Teh-tehan (Acalypha siamensis), Pisang Hias (Calathea lutea), Puring tokek (Codiaeum variegatum), Lengkuas Merah (Alpinia purpurata), Song of India (Dracaena reflexa), Palem Sadeng (Saribus rotundifolius), Puring Bali (Codiaeum variegatum), Mahoni (Swietenia mahagoni), Trembesi (Samanea saman), Soka (Ixora coccinea), Bintaro (Cerbera manghas) dll. Berdasarkan hasil pengamatan dilokasi penelitian dapat disimpulkan bahwa karateristik penataan/tata letak veg¬etasi yang ada di median jalan utama Kota Malang sudah cukup bagus hanya perlu penataan yang lebih rapi sehingga dapat lebih memperindah dan meningkat¬kan nilai estetika jalur hijau di Jalan Veteran Kota Malang.